Comparative Transcriptomic Analysis Reveals the Immunosuppressive Targets of Mesalazine in Dextran Sulfate Sodium-Induced Ulcerative Colitis - Li, Rong; Cheng, Lin; Wang, Qi; Zhou, Liming (Frontiers in Genetics, 2021)
Ulcerative colitis (UC) is a complex inflammatory bowel disorder that can induce colonic and rectal dysfunction. Mesalazine, a first-line medicine, is routinely prescribed for UC treatment. However, the pharmacological targets of mesalazine against UC are not detailed in the current publications. In the current study, a transcriptomics strategy was applied to reveal the therapeutic targets and molecular mechanisms of mesalazine for treating dextran sulfate sodium (DSS)-induced UC in mice. Compared with the UC group, a total of 1663 differentially expressed genes were identified in mesalazine-treated mice, of which 262 were upregulated and 1401 were downregulated. GO and KEGG enrichment analyses indicated that the protective actions of mesalazine for treating UC were related to the functional regulation of immune inflammatory response, such as the regulation of T cells, white blood cells, and cytokine receptor pathways. In addition, ingenuity pathway analysis of the gene network further revealed the inhibitory action of mesalazine on C-C motif chemokine ligands (CCL11, CCL21) and C-X-C motif chemokine ligands (CXCL3 and CXCR2). Taken together, the current transcriptomic findings revealed anti-UC pharmacological targets, including the newly discovered biotargets CCL11, CCL21, CXCL3, and CXCR2, of mesalazine against DSS-induced intestinal inflammation.